Simultaneous determination of zinc, copper, lead, and cadmium in fuel ethanol by anodic stripping voltammetry using a glassy carbon-mercury-film electrode - de Oliveira, M. F.; Saczk, A. A.; Okumura, L. L.; Fernandes, A. P.; de Moraes, M.; Stradiotto, Nelson Ramos [UNESP] (Springer, 2004)
A new, versatile, and simple method for quantitative analysis of zinc, copper, lead, and cadmium in fuel ethanol by anodic stripping voltammetry is described. These metals can be quantified by direct dissolution of fuel ethanol in water and subsequent voltammetric measurement after the accumulation step. A maximum limit of 20% (v/v) ethanol in water solution was obtained for voltammetric measurements without loss of sensitivity for metal species. Chemical and operational optimum conditions were analyzed in this study; the values obtained were pH 2.9, a 4.7-mum thickness mercury film, a 1,000-rpm rotation frequency of the working electrode, and a 600-s pre-concentration time. Voltammetric measurements were obtained using linear scan (LSV), differential pulse (DPV), and square wave (SWV) modes and detection limits were in the range 10(-9)-10(-8) mol L-1 for these metal species. The proposed method was compared with a traditional analytical technique, flame atomic absorption spectrometry (FAAS), for quantification of these metal species in commercial fuel ethanol samples.
Keywords: alternative fuel; ethanol; heavy metals; mercury film electrode; anodic stripping voltammetry